Paradigma Sosial Profetik Dalam Orientasi Dakwah Di Indonesia - Abdul Aziz Harahap; Alfiandri Setiawan (POROS ONIM: Jurnal Sosial Keagamaan, 2022)
The tendency of Islamic da'wah activities that are intolerant, racist and full of violence, both verbal and non-verbal, pose a threat to harmonious life in the pluralistic social life of Indonesian society. In response to this, the Indonesian Ulema Council (MUI) in 2017 formulated guidelines for preachers in Indonesia. The guidelines are projected as a code of ethics for preachers (da'i) in Indonesia. This qualitative research in the form of a literature study aims to identify the existence of the dimensions of prophetic Islamic social values in the orientation of da'wah in Indonesia formulated by the MUI. This study uses a normative-philosophical approach. The analytical theory used is the prophetic social values conceptualized by Kuntowijoyo in the idea of prophetic social science. The results of the study show that there are dimensions of prophetic Islamic social values in the orientation of da'wah in Indonesia formulated by the MUI. First, the value of transcendence in the formation of the religious-humanist personality of Muslims. Second, the value of liberation in shaping the personality of Muslims who are nationalist and pluralist. Third, the value of humanization in the formation of an innovative and harmonious Muslim personality. The theoretical implication of this research shows that the prophetic social values of Islam can be the basis of values or paradigms in realizing a moderate and peaceful Islamic da'wah. The limitation of this research is that it has not examined the form of the Indonesian government's political policy in mainstreaming Islamic prophetic social values for preachers in Indonesia.